Exposure to human bacterial pathogens in solid waste collection - MERTOĞLU, BÜLENT (My University, 2022)
Human-sourced wastes seriously threaten human health and natural balance. Waste Workers are exposed to biological, chemical and physical risk factors during the collection and processing of waste. This study focused on biological risk factors, which are one of the risk factors faced by solid waste collectors. Biological samples were taken from the hands, gloves, respiratory areas of waste workers and waste collection vehicles before and after the work in two different periods as hot and cold. As a result of the study, a total of 29 different bacterial species that have a clinical significance defined as a pathogen or opportunistic pathogen have been identified that may create a threat to workers\" health. This research results show that, working conditions should be regulated in waste collection works and human-pathogen interaction should be minimized. It was aimed to raise awareness for the protection and improvement of workers and public health.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Aquatic Science; Nature and Landscape Conservation; Environmental Science (miscellaneous); Physical Sciences; Life Sciences; Solid waste; biological risk; occupational health and safety; worker health; public health; bacterial pathogens; STENOTROPHOMONAS-MALTOPHILIA; STAPHYLOCOCCUS-WARNERI; BACILLUS-CEREUS; LEUCONOSTOC-MESENTEROIDES; OCCUPATIONAL-HEALTH; INFECTION; WORKERS; EPIDEMIOLOGY; SEPSIS; IMPACT